The Influence Of Self-Efficacy And Work Discipline On Employee Monthly Income Achievement In The Jababeka Cikarang Area - Rustomo, Rustomo; Hasanah, Uswatun; Rahayu, Tutik (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
control oneself as an employee and high work discipline in the Jababeka Cikarang area, which is one of the promising areas and provides various types of work that they can have and contribute to earning a monthly income, is the aim of this research. Quantitative method of survey study with employee respondents who work in the Jababeka Cikarang area whose population not yet known, the accidental sampling technique is a technique for determining samples based on chance, by distributing questionnaires using a Likert scale. By analyzing the data, we look for the influence and relationship between the magnitude of the contribution of the two independent variables to the dependent. The results of the validity and reliability test of the instrument were declare valid and reliable, all data were normal and there was no heteroscedasticity. Self-efficacy and work discipline on employee monthly income achievements in the Jababeka Cikarang area have a moderate relationship and have a significant positive effect.